(untitled) (Iranian Journal of Kidney Diseases, 2021)
Introduction. Estimating glomerular filtration rate (eGFR) using different formulas is common clinical practice for evaluating kidney function and drug dosing. But, the performance of available eGFR equations is questionable during early days after kidney transplantation. Methods. This study compared the performance of three common eGFR equations (Cockcroft-Gault (CG), Modification of Diet in Renal Disease (MDRD), and Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI)) in relation with measured GFR (mGFR) using clearance of Tc-99m-diethylenetriaminepentaacetic acid, 7 to 10 days post kidney transplantation. Agreement of mGFR and different eGFR equations in the staging of kidney function and dosing of 8 common antimicrobials were assessed. Result. Thirty kidney and 5 simultaneous pancreas-kidney transplant recipients were included. CG applying total body weight (CGTBW) had the lowest bias (-12 mL/min/ 1.73 m2) and the highest percentage of estimation within 30% of mGFR (71.4%). MDRD showed the best precision (13.14 mL/min/ 1.73m2) and linear correlation with mGFR. CKD-EPI and MDRD acted better than CG for staging the level of kidney function. CGTBW had the lowest discordance rate with mGFR for antimicrobials dosing (33.6%). Discordance rates of drug dosing between mGFR and eGFR formulas were greater for drugs that have higher dosing levels such as (val)-ganciclovir (≥ 54.3%). Conclusion. Until developing more accurate methods for estimating kidney function during first 1 to 2 weeks after kidney transplantation, CGTBW method is suggested for drug dose adjustment and MDRD or CKD-EPI equation for the staging of kidney function in these patients, keeping in mind that these formulas underestimate the level of kidney function in new transplant recipients.